2016
DOI: 10.4238/gmr.15017184
|View full text |Cite
|
Sign up to set email alerts
|

PI3K, AKT, and P-AKT levels in thin endometrium

Abstract: ABSTRACT. The aim of this study was to explore the expression of PI3K, AKT, and P-AKT, and to investigate the role of PI3K/AKT signaling pathway in thin endometrium. We included 40 women treated in affiliated Shenzhen Nanshan People's Hospital of Guangdong Medical University for endometrial conditions between August 2013 and January 2015, 20 with a normal endometrium, and 20 with thin endometrium. The expression of PI3K, AKT, and P-AKT was evaluated by the immunohistochemical S-P method. The expression of PI3K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…For example, rapid activation of PI3K/Akt signaling cascades by growth factors and estrogen is involved in the migration of normal endometrial stromal cells (Gentilini et al, 2007). However, the expression of DEGs in the PI3K/AKT pathway, including EFNA1, FGF9, LPAR1, CCNE2, SGK1, MET, IL6R, and PDGFRA, was decreased in thin endometrium, which suggests that the repair ability of the thin endometrium was impaired during the proliferative phase (Le et al, 2016). Similarly, the abnormal Wnt/beta-catenin signal pathway would also impair the proliferation of estrogendependent endometrial cells (Tepekoy et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…For example, rapid activation of PI3K/Akt signaling cascades by growth factors and estrogen is involved in the migration of normal endometrial stromal cells (Gentilini et al, 2007). However, the expression of DEGs in the PI3K/AKT pathway, including EFNA1, FGF9, LPAR1, CCNE2, SGK1, MET, IL6R, and PDGFRA, was decreased in thin endometrium, which suggests that the repair ability of the thin endometrium was impaired during the proliferative phase (Le et al, 2016). Similarly, the abnormal Wnt/beta-catenin signal pathway would also impair the proliferation of estrogendependent endometrial cells (Tepekoy et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The resulting production of SOD, CAT, GSH, and GSH-Px reduces oxidative stress damage to cells (Wen et al, 2018). Therefore, the activity of PI3K/Akt signaling pathway is usually expressed by the level of downstream p-Akt, where high expression of p-Akt indicates that the pathway is activated (Le et al, 2016). In our study, we found that the protein expression of PI3K, p-Akt, and Nrf2 was significantly reduced in the NTDs mouse embryonic model induced by atRA, suggesting that the PI3K/Akt signaling pathway was inhibited.…”
Section: Discussionmentioning
confidence: 99%
“…In present study, we evaluated the function of AKT and AKT1 in renal cell carcinoma. In addition, it was reported that the expression of AKT was positively correlated with the expression of p-AKT [ 20 ], which suggested AKT and p-AKT had the similar research value. In present study the antibody of total AKT was used in cellular experiments, based on the findings of in vitro experiments and previous studies, AKT1 was involved in regulating cell growth and proliferation, so we explored expression of AKT1 in human tissues by IHC staining.…”
Section: Discussionmentioning
confidence: 99%